Thermal treatments and germination response over time of seeds from serotinous and non serotinous cones of Pinus halepensis Mill. - Lovreglio R.; Salvatore R.; Giaquinto P.; Leone V. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Germination values of seeds of Pinus halepensis Mill. at different temperatures, times of exposure and different times of storage have been analysed. Strobila for testing were collected from a natural Aleppo pine seed-forest growing on dune sands in the South of Italy, separately considering young (brownish) and old (greyish) strobila, the latter considered serotinous. Both free seeds, extracted after oven exposure, and seeds that were still encased in intact strobila, were used. Combinations of temperature and time of exposure where selected to simulate the effect of surface fires on the crown and on the soil seed bank. Germinations values were analysed after 1,6 and 24 months of treatment in order to consider the effect of aging, both on soil and crown seed bank. A mixture of moderate temperatures and short exposure confirms a stimulating effect of thermal stress, which increases germination and has been already observed for many Mediterranean species. Only temperatures from 170° and above, even for brief exposure, cause a marked decrease in germination values. Woody strobila protect encased seeds, allowing them to perform excellent germination values at temperatures of 220° and more, with exposure times up to 3' which simulate a rather intense but slow running fire. Seeds from serotinous cones always exhibit the best results. Germination values remain rather stable over time, concluding that soil seed bank is almost unaffected by the passage of running fire and that seeds, still encased in strobila, stay vitality intact even in stands that appear to be dead.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)